Fostering Early Childhood Creativity through Finger Painting Activities: A Case Study - Fadia Haya, Auqillah; Ahmad, Alfandi; Putri Purnamasari, Dina; Aliya, Layyinatul; Lailatul Musfidah, Uun (Nak-Kanak: Journal of Child Research, 2025)
Background of the study: Art development is essential in early childhood education as it allows children to express their creativity and imagination. By the age of 5–6 years, children are expected to create diverse drawings and paintings using various techniques. However, in Class B at TK Pratiwi Kamal, several children had not yet developed the ability to produce painting works, indicating a gap in their artistic growth. This highlights the need for appropriate and engaging interventions to support their creativity. Aims and scope of paper: This study aims to examine the effectiveness of finger painting as a method to enhance painting skills and artistic creativity among 5–6-year-old children. The focus is specifically on Class B at TK Pratiwi Kamal, with finger painting used as a medium to support visual art expression in early learners. Methods: The research uses a Classroom Action Research design. The subjects were seven children—three girls and four boys—who participated in finger painting activities. Data collection involved observation and performance assessments to evaluate changes in artistic abilities before and after the intervention. Results: The results showed varied levels of development: two children were in the "Not Yet Developed" category, one in "Beginning to Develop", two in "Developing as Expected", and two in "Very Well Developed". These findings indicate that finger painting positively impacted the children’s artistic abilities, though progress differed among individuals. Contribution: This study highlights finger painting as a valuable tool in fostering creativity and imagination in early childhood. It underlines the importance of providing diverse art media in early education. Teachers and schools are encouraged to integrate such methods to nurture artistic development and support children’s talents from an early age.